Academic Writing in the Age of AI: Formulating Responsible Use Strategies to Preserve Academic Integrity in Arabic Higher Education - Ahmad Rifa'i; Anggi Nurul Baity; Aulia Golda Mutarto; Cika Apriska M.D Umar; Alfana Salsabila; Fadia Iftakhul Adlya (Asalibuna, 2026)
The integration of Artificial Intelligence (AI) into students’ academic writing provides significant support for the development of ideas and linguistic accuracy. However, its indiscriminate and uncontrolled use risks undermining originality and academic integrity. This study examines patterns of AI utilisation, perceptions of academic integrity, and formulates strategies for the ethical and effective use of AI amongst students on the Arabic Language Education programme at UIN Syekh Wasil Kediri. Employing a qualitative descriptive design, this study involved 63 students and 4 lecturers teaching academic writing courses. Data were collected via an online questionnaire, in-depth interviews and classroom observations, and were subsequently analysed thematically. The research findings indicate that students actively utilise various AI platforms, such as language chatbots, machine translators and grammar checkers, as writing aids. However, this pragmatic and instantaneous pattern of use tends to undermine critical thinking, the depth of argumentation and intellectual independence, even though students are aware of the ethical risks involved. This study emphasises the need for programme-level strategies that integrate AI literacy and academic ethics, establish clear guidelines for use, and position AI as a cognitive partner rather than a substitute for the thinking process. This step is crucial for strengthening responsible academic writing practices in higher education.   Abstrak:  Integrasi Artificial Intelligence (AI) dalam penulisan akademik mahasiswa memberikan dukungan signifikan pada pengembangan ide dan akurasi linguistik. Namun, penggunaan yang instan dan tidak terkendali berisiko mengancam orisinalitas serta integritas akademik. Penelitian ini mengkaji pola pemanfaatan AI, persepsi integritas akademik, serta merumuskan strategi penggunaan AI yang etis dan efektif di kalangan mahasiswa Program Studi Pendidikan Bahasa Arab UIN Syekh Wasil Kediri. Menggunakan desain deskriptif kualitatif, studi ini melibatkan 63 mahasiswa dan 4 dosen pengampu mata kuliah penulisan akademik. Data dikumpulkan melalui kuesioner daring, wawancara mendalam, serta observasi kelas, lalu dianalisis secara tematis. Hasil penelitian menunjukkan bahwa mahasiswa secara aktif memanfaatkan berbagai platform AI seperti chatbot bahasa, penerjemah mesin, dan pemeriksa tata bahasa sebagai alat bantu penulisan. Meski demikian, pola penggunaan yang pragmatis dan instan cenderung melemahkan pemikiran kritis, kedalaman argumentasi, dan kemandirian intelektual, sekalipun mahasiswa memahami risiko etisnya. Studi ini menegaskan perlunya strategi tingkat program yang mengintegrasikan literasi AI dan etika akademik, menetapkan pedoman penggunaan yang jelas, serta memposisikan AI sebagai mitra kognitif bukan pengganti proses berpikir. Langkah ini penting untuk memperkuat praktik penulisan akademik yang bertanggung jawab dalam pendidikan tinggi.